The Influence of Socio-Economic, Marital Status, Education, and Wages on Repeat Migration Decisions of Indonesian Migrant Workers in Kawo Village, Pujut District, Central Lombok Regency - Widarni, Baiq; Arini, Gst Ayu; Husni, Vici Handalusia (Westscience Press, 2025)
This study aims to empirically test the influence of socio-economic, marital status, education, and wages on the decision to repeat migration of Indonesian Migrant Workers in Kawo Village, Pujut District, Central Lombok Regency. The sample of this study was Indonesian Migrant Workers in Kawo Village, Pujut District, Central Lombok Regency who had been Indonesian Migrant Workers more than once. Data collection was carried out by questionnaires distributed directly to Indonesian Migrant Workers in Kawo Village, Pujut District, Central Lombok Regency as many as 45 respondents. The statistical method used logistic regression analysis (binary logistic), simultaneous test, partial test (f test) and pseudo R² with the results of socio-economic has a significant negative effect on the decision to repeat migration of Indonesian migrant workers in Kawo Village, Pujut District, Central Lombok Regency, education has a significant positive effect on the decision to repeat migration of Indonesian migrant workers in Kawo Village, Pujut District, Central Lombok Regency, marital status, and wages do not significantly affect the decision to repeat migration of Indonesian migrant workers in Kawo Village, Pujut District, Central Lombok Regency.